STUDI ALIH FUNGSI LAHAN DARI LAHAN SAWAH KEPUSAT PERDAGANGAN DI KANAGARIAN SURIAN KECAMATAN PANTAI CERMIN KABUPATEN SOLOK - -, Nofermaliza - (STKIP PGRI Sumbar, 2014)
The problem in this study is how the level of income and education before and after theconversion of paddy land went to the trade in Kenagarian Surian Subdistrict Pantai Cermin DistrictSolok. This study aimed to describe income levels before and after the conversion of wetland totrade center in Kenagarian Surian Subdistrict Pantai Cermin District Solok. This type of researchin this study was a descriptive study. population in this study was a community that doesconversion of paddy fields into a trading center in Kenagarian Surian Subdistrict Pantai CerminDistrict Solok as many as 134 people. Samples were taken by purposive (designation) as many as66 people. Types of primary and secondary data. Techniques of data collection usingquestionnaires. Instrument research using questionnaires. Analysis using a percentage formula.Theresults show that income and education before and after the conversion of wetland trade center inKenagarian Surian Subdistrict Pantai Cermin District Solok. increased. Income communities priorto conversion of paddy fields into commercial centers, including category (45%) with an averagespending of Rp. 3,199,167, the highest production of Rp. 21.3 million and expenditures of at leastRp. 425,000. After the conversion of paddy fields to the trading center include many categories(56%) with an average expenditure of Rp. 4,001,755, the highest production of Rp. 51,558,000and expenditures of at least Rp. 681,300. Prior to conversion of paddy fields to the commercialcenter of the community, including enough to know (40%), knowledge about how to clear land89.4%, harvested only twice a year, 84.8%, using labor (service people) 56.1 % of revenue in oneyear â¥1500kg 39.4%, and the state of the environment, including good category of 74.2%. Afterthe conversion is categorized know better (60%), knowledge about how to clear land 50%,harvested only twice a year to 84.8%, the energy, the car 50% of income in a year of 800 kg to1000 kg 51.5 %, and the state of the environment, including the unfavorable category of 37.9%.